Decreased Neurofilament L Chain Levels in Cerebrospinal Fluid and Tolerogenic Plasmacytoid Dendritic Cells in Natalizumab-Treated Multiple Sclerosis Patients – Brief Research Report - Moraes, Adriel S.; Boldrini, Vinicius O.; Dionete, Alliny C.; Andrade, Marilia D.; Longhini, Ana Leda F.; Santos, Irene; Lima, Amanda D. R.; Silva, Veronica A. P. G.; Dias Carneiro, Rafael P. C.; Quintiliano, Raphael P. S.; Ferrari, Breno B.; Damasceno, Alfredo; et al. (Frontiers in Cellular Neuroscience, 2021)
Background: Neurofilament Light (NfL) chain levels in both cerebrospinal fluid (CSF) and serum have been correlated with the reduction of axonal damage in multiple sclerosis (MS) patients treated with Natalizumab (NTZ). However, little is known about the function of plasmacytoid cells in NTZ-treated MS patients. Objective: To evaluate CSF NFL, serum levels of soluble-HLA-G (sHLA-G) and eventual tolerogenic behavior of plasmacytoid Dendritic cells (pDCs) in MS patients during NTZ treatment. Methods: CSF NFL and serum sHLA-G levels were measured using an ELISA assay, while pDCs (BDCA-2+) were accessed through flow cytometry analyses. Results: CSF levels of NFL were significantly reduced during NTZ treatment, while the serum levels of sHLA-G were increased. Moreover, NTZ treatment enhanced tolerogenic (HLA-G+, CD274+, and HLA-DR+) molecules and migratory (CCR7+) functions of pDCs in the peripheral blood. Conclusions: These findings suggest that NTZ stimulates the production of molecules with immunoregulatory function such as HLA-G and CD274 (PD-L1) which may contribute to the reduction of axonal damage represented by the decrease of NFL levels in patients with MS.